Composition of nickel chlorid hydrate and nickel aluminium oxide – the novel catalyst for hydrogenation - Long, Ho Son; Chau, Tran Boi; Cong, Huynh Thanh; Minh Hoang, Vo Do; Lam, Ho Son (Vietnam Journal of Chemistry, 2012)
New catalysts based on nickel chlorite and aluminum chlorite are aggregated over the period to create complex, then sintered at a temperature of 550oC. The results analyzed by IR, X-ray, BET and SEM showed many similarities between the new catalysts with catalyst Ranay-nickel Merck’s standards. Both catalysts are used to carry hydrogenation reaction in the gas phase and in the liquid phase in the autoclave with 2 atm pressure, on the same object as citronella essential oil content of 86% citral. Of the reaction products were analyzed on GC/MS HP 6890 with column HP5MS using helium gas bearing. Products of the reaction showed efficient catalytic hidro genation of these new catalysts are not inferior to standard Ranay-nickel, but also created many other precious products, especially when the liquid phase hidro genation of 2 atm pressure.